MyRental4U for landlords and tenants: Enhanced conceptual business model - Amin, Muhamad Amiruddin; Zaini, Muhamad Zahiruddin; Ahmad Dahlan, Abdul Rahman; Mohd Tamrin, Mohd Izzuddin (Research Publish Journal, 2018)
This paper proposes a conceptual solution to help people to overcome the communication problem among landlords and tenants by providing them an effective application through mobile application-based platform “MyRental4U”. “MyRental4U” is a business model which provides a digital platform for tenants to communicate with their landlords without meeting them face to face. “MyRental4U” also provides the opportunity for landlord by providing them a platform to maintain their business to the customers. Nine blocks of Business Model Canvas (BMC) framework, Literature Review, strategy canvas, value proposition design canvas (VPC), environmental map and conducting interview/survey with potential customers to validate BMC/VPC have been used as the methodologies for this paper.